Academic Supervisory Management in Improving the Quality of Teacher Performance at MAN Tarakan - Nuraini Nuraini (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the implementation of academic supervision management by supervisors and its implications for improving teacher performance quality at Madrasah Aliyah Negeri (MAN) Tarakan. Academic supervision is a strategic instrument in the educational quality assurance system carried out by madrasah supervisors. This research employs a descriptive qualitative approach with data collection through observation, in-depth interviews, and documentation. Research subjects included madrasah supervisors, the principal, and teachers of MAN Tarakan. The results indicate that academic supervision management at MAN Tarakan encompasses the stages of supervision program planning, implementation through classroom visits, learning observation, and professional guidance, as well as follow-up in the form of coaching and evaluation. Systematically and sustainably implemented academic supervision has been proven capable of improving teachers' pedagogical competence, quality of lesson planning, effectiveness of classroom instruction, and teacher motivation and work ethic. These findings affirm the critical role of supervisors as professional supervisors within the madrasah quality improvement ecosystem.